Mechanism of Application for Overbooking Via E-Pbk for Errors in Filling in E-Billing Data at the Pratama Tax Service Office xxx - Safrizal; Maulana Pratama , Rizal; Rasmon; Jonnedi (Journal Economic Business Innovation, 2024)
In general, taxes are mandatory contributions from the people to the government that are coercive and regulated by law. In tax administration, taxpayers are required to pay or deposit the tax owed through a Surat Setoran Pajak (SSP) to the state treasury via a payment location. In connection with the Direktorat Jenderal Pajak No 26 Tahun 2014 concerning Electronic Tax Payment Systems, a tax payment system called E-Billing has also come into effect. E-Billing is a method of paying taxes electronically using a Billing Code. In the E-Billing payment process, if a taxpayer experiences problems in entering their tax data incorrectly, the Taxpayer is given the facility to submit an Overbooking application. Overbooking is defined as a process of transferring tax receipts to be recorded in the appropriate tax receipts. And starting December 12 2022, the Directorate General of Taxes will release E-Pbk (electronic book transfer). E-Pbk is an abbreviation for electronic book transfer. E-Pbk itself is an application that taxpayers can use to request transfers electronically without having to queue in Tax Service Office. The research purposes this writing is to find out about the Mechanism of Application for overbooking via e-pbk for errors in filling in e-billing data at Tax Service Office xxx. The data collection method used is a qualitative method, which is a research method that deals with unstructured data and non-numerical data, for example videos, images and text. Meanwhile, the data collection technique in this writing is using interviews and documentation. And for the result, we can see that the mechanism for requesting book transfers via e-pbk at the Tax Service Office starts with the taxpayer having to first have a DJP Online account via the website https://djponline.pajak.go.id/. Then the taxpayer must prepare the files that will be transferred, in this case it is an error in making E-Biling. After successfully logging in and activating the E-Pbk facility in the menu at DJP Online, taxpayers can apply for book transfers online without attend to the Tax Services Office. And within a maximum of 21 working days from the application via E-Pbk, the taxpayer will receive the transfer results by post/can be taken directly to the registered tax office